A note on the matching preclusion number of caylay graphs on Abelian groups with given degree - Zhang, Xiaojuan, (Utilitas Mathematica, 2022)
The matching preclusion number of a graph is the minimum number of edges whose deletion results in a graph that has neither perfect matchings nor almost-perfect matchings. For many interconnection networks, the optimal sets are precisely those induced by a single vertex. In this paper we study this invariant for Cayley graphs on Abelian groups with degree 3,4. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.